A compreensão das lideranças no desenvolvimento profissional dos professores - Oliveira, Conceição de (2021)
In an increasingly connected and interdependent society, collaborative culture emerges as an effective and efficient answer to overcome the complexities that teachers face daily. In turn, the teaching activity requires a continuous reflection on practice, involving the teacher in a constant search for professional development, as a reflective researcher. Now, the action of teaching, understood as a craft and an art that materializes in practices, requires grounding (specific knowledge and skills), theoretical-practical reflection, aimed at improving the teaching and learning of students. For this purpose, the school must be thought of as a learning organization that expands and innovates with the development of professionals who work in it, which requires a new mode of operation from the leaders, the creation of favorable conditions for the continuous questioning of practices and a culture that values permanent learning and improvement. The study carried out in a group of schools in the Greater Lisbon area had, among others, the following objectives: i) to identify the perceptions of leaders about supervision and collaboration; and iii) understand the role of leaders in the professional development of teachers. From a methodological point of view, the investigation assumes the design of a case study, with a mixed approach, based on eight individual interviews with top leaders and twenty-one questionnaire surveys, applied to class directors. The results show different understandings about the concept of collaboration and the role of leaders in the professional development of teachers, perceived as an unfinished process and under permanent reconstruction.